Targeting subsidised inpatient services to the poor in a setting with limited state capacity: proxy means testing in Myanmar's hospital equity fund scheme. Issue 9 (30th July 2019) - Htet, Soe; Ludwick, Teralynn; Mahal, Ajay
Abstract: Objectives: Many low‐ and middle‐income countries (LMICs) provide subsidised access to health services for the poor. Proxy means tests (PMTs) for income are typically employed to identify eligible beneficiaries for subsidised services but often result in significant mistargeting of benefits. We assessed the PMT approach used in Myanmar's hospital equity fund (HEF). Methods: We analysed inclusion/exclusion errors by comparing household eligibility under the PMT used for HEF with household consumption (the gold standard proxy for income in LMICs). We assessed receipt of benefits post‐hospitalisation against HEF eligibility rules and household income. Focus groups/interviews were conducted to understand administrative factors that influence targeting. We modelled (linear regression) predictors of household consumption to improve PMT accuracy. Results: We found large targeting errors (86% of households in the bottom consumption quartile would be excluded and 15% of households in the top consumption quartile deemed eligible). HEF scores for PMT held little explanatory power for household income: 93% of individuals meeting the HEF eligibility criteria did not receive benefits post‐hospitalisation, while 23% of ineligible individuals received programme support. Re‐weighting PMT indicators on electricity access, land ownership and livestock ownership, and assigning weights to home‐ownership, households with elderly/disabled members and household head education levels could significantly improve targeting accuracy. Poor programme awareness and uneven adherence to official eligibility determination procedures among staff likely affected targeting. Conclusions: Re‐weighting PMT indicators and increasing training and communication about qualification procedures could improve allocation of limited funds, though accurate targeting may continue to be challenging in contexts of low state capacity. Abstract : Objectifs: De nombreux pays à revenu faible ou intermédiaire (PRFI) offrent un accès subventionné aux services de santé pour les pauvres. Les tests des proxys moyens (TPM) de revenus sont généralement utilisés pour identifier les bénéficiaires éligibles pour les services subventionnés, mais aboutissent souvent à un ciblage erroné important des avantages. Nous avons évalué l'approche TPM utilisée dans le fonds d'équité des hôpitaux (FEH) du Myanmar. Méthodes: Nous avons analysé les erreurs d'inclusion/exclusion en comparant l'éligibilité d'un ménage selon le TPM utilisé pour le FEH avec la consommation du ménage (indicateur de référence par excellence du revenu dans les PRFI). Nous avons évalué la réception des prestations après l'hospitalisation par rapport aux règles d'éligibilité du FEH et au revenu du ménage. Des discussions de groupes ont été menées pour comprendre les facteurs administratifs qui influencent le ciblage. Nous avons modélisé (régression linéaire) les prédicteurs de la consommation des ménages afin d'améliorer la précision du TPM. Résultats: Nous avons constaté d'importantes erreurs de ciblage (86% des ménages du quartile de consommation le plus bas seraient exclus et 15% des ménages du quartile de consommation le plus haut jugés éligibles). Les scores FEH du TPM ont peu de pouvoir explicatif sur le revenu du ménage: 93% des personnes répondant aux critères d'éligibilité du FEH ne bénéficiaient pas de prestations post hospitalisation, tandis que 23% des personnes non éligibles recevaient un soutien du programme. La repondération des indicateurs du TPM sur l'accès à l'électricité, la propriété foncière et la propriété du bétail, et l'attribution de pondérations à la propriété du logement, aux ménages composés de personnes âgées/handicapées et au niveau d'éducation des chefs de ménage pourraient améliorer considérablement la précision du ciblage. La faible sensibilisation du programme et le respect inégal des procédures officielles de détermination de l'éligibilité parmi le personnel ont probablement affecté le ciblage. Conclusions: Une repondération des indicateurs du TPM et une augmentation de la formation et de la communication sur les procédures de qualification pourraient améliorer l'allocation de fonds limités, bien qu'un ciblage précis puisse continuer à être un défi dans des contextes de faible capacité de l'Etat.